2016
DOI: 10.1161/atvbaha.116.307870
|View full text |Cite
|
Sign up to set email alerts
|

New View on Endothelial Cell Migration

Abstract: A ngiogenesis, the formation of new blood vessels from pre-existing ones, is essential during development and wound healing and in diseases, such as cancer. Invasion into and migration through the extracellular matrix (ECM) are mandatory for endothelial cells (ECs) to assemble a vascular system. Thus, there is tremendous interest in understanding the properties and behavior of ECs in 3-dimensional (3D) environments.The basic concepts underlying EC migration have mostly been gleaned from observations in 2D cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…48,49 Sustained ROS levels can contribute to the endothelial dysfunction, and further to its senescence and activation of an inflammatory response, and in turn lead to the development of atherosclerosis. NADPH oxidases, especially Nox4, play an ambiguous role in the development of atherosclerosis.…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…48,49 Sustained ROS levels can contribute to the endothelial dysfunction, and further to its senescence and activation of an inflammatory response, and in turn lead to the development of atherosclerosis. NADPH oxidases, especially Nox4, play an ambiguous role in the development of atherosclerosis.…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…where λ f the strength and direction of the force, and p(i) and p(j) are the positions of target voxel and source voxel, respectively, during index-copy attempts. Assuming a maximum velocity of 0.3 µm/min for the cells (Kick, Nekolla, Rehberg, Vollmar, & Zahler, 2016b), the cell velocity trial tests indicated that the maximum λ f value that could be employed would be approximately 160.…”
Section: Cellular Potts Modelmentioning
confidence: 99%
“…We assess the intensity of fibrosis with the fiber field value and use 75% of the maximum fiber field value as a threshold. For cells trapped in calcified or fibrotic regions, we use a cell velocity threshold of 0.003 µm/min (1% of the maximum cell velocity) for determining insignificant cell movement (Kick, Nekolla, Rehberg, Vollmar, & Zahler, 2016a).…”
Section: Calcification Modelmentioning
confidence: 99%
“…49,50 Another study showed that engagement of the matricellular protein thrombospondin-1 with CD47 activated NOX1, 51 an important finding, given that vascular matrices contribute heavily to the progression of diseases. 52 Cyclic stretch in vessels induces MEF2B, which subsequently induces NOX1, and this has been identified as a necessary pathway for cyclic stretch-induced phenotypic switching of VSMC’s to a proliferative state. 53 Similarly, both NOX1 and NOX4 isoforms are upregulated by high plasma glucose concentrations.…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%